Learning adaptation during the COVID-19 pandemic in Muhammadiyah inclusion schools - Sri Lestari; Waode Hamsia; Radius Setiyawan (Intelektual Pustaka Media Utama, 2021)
The Muhammadiyah organization has inclusive schools that need to adapt during the coronavirus disease 2019 (COVID-19) pandemic. This study aimed to analyze the adaptation strategies carried out by two Muhammadiyah inclusion schools in Surabaya, Indonesia, Sekolah Peduli Anak Hebat (SPAH) and the Sekolah Kreatif Surabaya. This study used a qualitative descriptive approach with a phenomenology method to see the particular context of the two inclusion schools' learning situation during the COVID-19 pandemic. The data were collected using interviews and observations. Two coordinators for students with disabilities and five teachers were interviewed about policies and learning processes during the pandemic. The observation was done during the learning process. The secondary data was also collected by searching in their social media and e-learning platforms. The data analysis showed that the adaptation strategies were to coordinate and regularly collaborate between parent-teachers-students, build community cooperation, and make flexible and accessible learning policies. It proved that the two Muhammadiyah inclusion schools in Surabaya had adapted to online learning during the pandemic COVID-19. However, the two schools still need to improve quality, especially in creating an accessible asynchronous learning platform for students with disabilities.